Managing Employee Diversity for Effective Productivity in Secondary School in Rivers State, Nigeria - Iibi, John (NIU Journal of Social Sciences, 2019)
There is increasing observation that diverse employee management pose challenges and threats to effective school administration and management in Nigeria. The paper examined managing employee diversity for effective productivity in secondary schools in Rivers State. However, in order to achieve this, the paper considered the following: the introduction to the study, conceptual clarification of management, diversity management and effective productivity. This paper considers incentives and motivation as a meansof encouragement to take action, these are direct and indirect benefits offered to employees. They are two types of incentives, monetary and non-monetary. The paper also discussed the strategies of managing employeeâ€™s diversity. The paper suggested that schools and government should create and maintain policies guiding diversity management and employees in accordance to those differences as this will reduce if not eradicate discrimination, stereotypes and prejudice. Also that Rivers State is a multicultural state and such school administrators and policy makers should not carry their cultural experiences and perspectives to their educational decisions and actions to avoid cultural conflicts in a pluralistic school environment. Keywords:  Management, Diversity, Employees Diversity, Effective productivity